Pengaruh Budaya Organisasi dan Iklim Organisasi terhadap Kinerja Pegawai Dinas Sosial Kota Depok - Hana Luthfiyyah (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
The Social Service Office of Depok City is a regional government agency that plays a strategic role in formulating, coordinating, and implementing social development policies to improve the quality of life and welfare of the community in Depok City. The objective of this research is to determine the influence of organizational culture on employee performance and the impact of organizational climate on the performance of employees at the Dinas Sosial Kota Depok. This study employs a quantitative approach using survey methods, with questionnaires as the primary instrument. The sampling technique used is saturated sampling, with a total of 37 respondents from the Social Service Office of Depok City. The data collected were analyzed using multiple linear regression with the help of SPSS version 25 software. Based on the results of this study, the organizational culture variable (X1) has a positive and significant effect on employee performance (Y), with a calculation result of t_count > t_table (3.558 > 1.690) and a significance level of 0.001 < 0.05. The organizational climate variable (X2) also has a positive and significant effect on employee performance (Y), as shown by the calculation result of t_count > t_table (2.540 > 1.690) with a significance level of 0.000 > 0.05. Simultaneously, the organizational culture variable (X1) and the organizational climate variable (X2) have a positive significant effect on employee performance (Y). This is supported by the calculation result of F_count of 28.428 with a significance level of 0.000 < 0.05 and F_count > F_table (28.428 > 3.27). The analysis of the coefficient of determination (R2) shows an R Square of 0.626 or 62.6%, influenced by the organizational culture variable (X1) at 37.4% (100% - 62.6%) and the organizational climate variable (X2) at an R Square of 0.586 or 58.6%, while the remaining 41.4% (100% - 58.6%) is influenced by other independent variables not examined in this study.